2011
DOI: 10.1007/s12011-011-9149-z
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: The Effect of Lead Acetate Toxicity on Experimental Male Albino Rat

Abstract: Background: Estrogen hormone and receptors (ER) play an important role in maintaining vaginal health. Therefore, their disruption may adversely affect vaginal structure and function. Limited studies are available investigating the effects of diabetic complications on ER expression and distribution in the vaginal wall. Aim of the Work: This work aimed to study the effects of diabetes-induced changes on the vaginal structure, the expression of ERα as well as to determine whether the supplementation of estradiol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 27 publications
(22 reference statements)
2
5
0
Order By: Relevance
“…These findings are in agreement with (Ibrahim et al, 2011) who found that lead caused decreases in rats' growth rate when fed on it. Also, agreed with(Seddik et al, 2010) who reported that chronic Pb exposure for 90 days was associated with a decrease in body weight gains when compared to control rats.…”
Section: Effect Of Fenugreek and Alfalfa Seeds On Body Weight Gain Fsupporting
confidence: 93%
“…These findings are in agreement with (Ibrahim et al, 2011) who found that lead caused decreases in rats' growth rate when fed on it. Also, agreed with(Seddik et al, 2010) who reported that chronic Pb exposure for 90 days was associated with a decrease in body weight gains when compared to control rats.…”
Section: Effect Of Fenugreek and Alfalfa Seeds On Body Weight Gain Fsupporting
confidence: 93%
“…The ingestion of lead acetate into male of albino rats caused decreases in the average gain of body weight and increased orangs weight increases in liver function in enzymes (ALT and AST) Activity and changed the lipid profile but total soluble protein and albumin contents of plasma were decreased and cholinesterase activity was inhibited, in contrast alkaline and acid phosphatases as well as LDH activities were increased (Abdel-Rahim et al 2014 ). The lead ingestion reduced the blood hemoglobin and RBC count under the same condition (Ibrahim et al 2011 ). The toxicity of lead is closely related to age, sex, route of exposure, level and frequency of intake, solubility, metal oxidation state, retention percentage, and duration of exposure and efficiency of excretion.…”
Section: Introductionmentioning
confidence: 88%
“…Pb(C 2 H 3 O 2 ) 2 alters biochemical and hematological profiles, revealing renal and hepatic toxicity via an increase in (ROS) formation and (OS), revealing an increase in lipid peroxidation and a decrease in GSH in renal and hepatic tissues ( Ibrahim et al, 2011 , Wang et al, 2011 , Liu et al, 2012 ). Ozsoy et al, (2011) Pb always causes biochemical and histological changes in the blood, kidney, liver, and brain tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Elmenoufy (2012) found that Pb treatment increased the creatinine, uric acid, bilirubin, and urea levels in exposed rats; moreover, Pb-exposed rats exhibited increased levels of total cholesterol, LDL, HDL, and TG, and also elevated ALP, GPT, and GOT enzymes. Pb(C 2 H 3 O 2 ) 2 altered hematological and biochemical profiles and revealed renal and hepatic damage via a significant increase in reactive oxygen species (ROS) formation, resulting in oxidative stress (OS), elevated lipid peroxidation, and a decrease in glutathione (GSH) levels in tissues ( Ibrahim et al, 2011 , Liu et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%